O regime jurídico da regulação econômica no setor de água e esgotamento sanitário sob a ótica do Novo Marco Regulatório - Gallacci, Fernando Bernardi (2022)
Under a legal perspective, this research will study the economic regulation regarding both water distribution and public sanitation. There work herein aims at describing the recent history of the sector regulation, its legal framework, and the guidelines of the object to be analyzed, encompassing the economic regulation. Based on these notions, the analysis moves forward to the legal regime for the economic regulation, which reflects the provision to preserve the economic and financial balance of the concession agreements regarding these public services, additionally to comply with accessible tariffs for users and the incentive to foster efficiency in the deliverables of the economic activities within water and sanitation. Upon such premises, it is analyzed Brazilian Federal Law No. 11,44/2007 and the new Regulatory Framework of Water and Sanitation, enforced by Brazilian Federal Law No. 14,026/2020. The study is conduct according to the assessment of both specialized literature and judicial case-law. At the end, it is expected to demonstrate a systemized overview of the main legal aspects of the economic regulation in the water and sanitation sector, as well as its’ debates, including those discussions raising directly or indirectly from the new legislation